In vivo and in vitro metabolism of the synthetic cannabinoid JWH‐200. (13th August 2013) - De Brabanter, Nik; Esposito, Simone; Tudela, Eva; Lootens, Leen; Meuleman, Philip; Leroux‐Roels, Geert; Deventer, Koen; Eenoo, Peter Van
Abstract : RATIONALE: The synthetic cannabinoid JWH‐200 (1‐[2‐(4‐morpholinyl)ethyl]‐3‐(1‐naphthoyl)‐indole) appeared on the market around 2009. In order to identify markers for misuse of this compound and allow for the development of adequate routine methods, the metabolism of this compound was investigated using two models. METHODS: In vitro and in vivo (both with and without enzymatic hydrolysis) samples were purified by solid‐phase extraction and analyzed using liquid chromatography. Electrospray ionization high‐resolution Orbitrap mass spectrometry was used for the identification of the metabolites. To confirm the results in vivo, triple‐quadrupole mass spectrometry was employed RESULTS: In the in vitro model, using human liver microsomes, 22 metabolites were detected which could be divided into 11 metabolite classes. By using the chimeric mouse model with humanized liver, most of these metabolites were confirmed in vivo . It was found that all metabolites are excreted in urine as conjugates, mostly as glucuronides with varying conjugation rates. CONCLUSIONS: The metabolite formed by consecutive morpholine cleavage and oxidation of the remaining side chain to a carboxylic group was detected in the highest amounts with the longest detection time. Therefore, it is the best candidate metabolite to detect JWH‐200 abuse in urine. Copyright © 2013 John Wiley & Sons, Ltd.